2018
DOI: 10.1177/1049732318800674
|View full text |Cite
|
Sign up to set email alerts
|

“It Changed Our Outlook on How We Want to Live”: Cancer as a Transformative Health Experience for Young Adult Survivors and Their Family Members

Abstract: Although young adult cancer survivors (YACSs) and their families face unique psychosocial and health-related challenges related to cancer, little is known about how the illness experience of cancer may positively transform their mental, physical, and social well-being following primary treatment. We conducted individual qualitative interviews with 30 YACSs and 21 of their family members. Participants described positive transformations as (a) perspective shifts on health and risk, (b) behavior changes toward mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
(93 reference statements)
0
11
0
1
Order By: Relevance
“…Our findings for EP being positively associated with resilience and PTG might also reflect a focus on the cancer experience as a transformative experience, a tangible change in relation to some sort of catalyst (e.g., changes experienced in postillness life), 34 that is fostered by an active attempt to acknowledge, explore, and understand one's emotions. Previous research among young adults with cancer has suggested that some young adults experience cancer as a positive transformative experience while others do not, often taking a fatalistic view of their cancer experience 35 . Drawing on current study findings fostering and encouraging EP may be one avenue to further understand how young adults restructure their cancer experience and themselves in positive ways.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Our findings for EP being positively associated with resilience and PTG might also reflect a focus on the cancer experience as a transformative experience, a tangible change in relation to some sort of catalyst (e.g., changes experienced in postillness life), 34 that is fostered by an active attempt to acknowledge, explore, and understand one's emotions. Previous research among young adults with cancer has suggested that some young adults experience cancer as a positive transformative experience while others do not, often taking a fatalistic view of their cancer experience 35 . Drawing on current study findings fostering and encouraging EP may be one avenue to further understand how young adults restructure their cancer experience and themselves in positive ways.…”
Section: Discussionmentioning
confidence: 55%
“…Previous research among young adults with cancer has suggested that some young adults experience cancer as a positive transformative experience while others do not, often taking a fatalistic view of their cancer experience. 35 Drawing on current study findings fostering and encouraging EP may be one avenue to further understand how young adults restructure their cancer experience and themselves in positive ways.…”
Section: Discussionmentioning
confidence: 85%
“…Similar to previous work (Chisholm, 2020;Head & Iannarino, 2019;Petrella et al, 2020;Wu et al, 2015), AYAs described being motivated to engage in PA to manage changes in body appearance and function, physical and mental health, and one's routine, independence, and sense of normalcy. Notably, the previously active AYAs were highly invested in their body's appearance and weight, which was integral to their decision to be active after treatment.…”
Section: Discussionmentioning
confidence: 60%
“…27 Meme kanseri tedavisini tamamlamış bireylerle yürütülen diğer nitel çalışmalarda da kanserden sağ kalan bireylerin sağlığa zararlı alışkanlıklarından kurtuldukları, sağlıklı yaşam biçimi davranışlarını benimsedikleri bildirilmiş, bireylerin tedavi sonrası süreçte hiçbir şeyi ertelemedikleri ve stresten uzak kalmaya çalıştıkları rapor edilmiştir. 19,27,29 Bu araştırmada katılımcılar, olaylara verdikleri duygusal tepkilerin değiştiğini, eskiye göre daha sinirli ve duygusal olduklarını ve daha kolay ağlayabildiklerini ifade etmişlerdir. Literatürde tedavi sonrası dönemde meme kanserli bireylerin, psiko-sosyal iyilik hâlinin etkilendiği ve duygu durumlarında değişim yaşayabildikleri bildirilmiştir.…”
Section: Discussionunclassified